Kajian peluang pengembang kewirausahaan perikanan berdasarkan karakter sosial ekonomi masyarakat di Dsa Santiri Kecamatan Tiworo Utara Kabupaten Muna Barat - Risjayanti; Yusuf, Sarini; Mansyur, Akhmad (Universitas Halu Oleo, 2021)
This research aims to determine the developer opportunities for fisheries entrepreneurship based on the socio-economic character of the community in Santiri Village, North Tiworo District, West Muna Regency. This research was conducted from March to April 2020. The sampling technique used a saturated sampling method or census. Data collection techniques used interviews, observation, and documentation. Data analysis used is PCA analysis (Principal component analysis). The results showed that the developer opportunities for fisheries entrepreneurship based on the socio-economic character of the community, namely having the potential to provide the ability to develop a business, which has the greatest opportunity is processing with a percentage of 90.6 %, trading 44.1% and catching 43.5%.